Teaching anthropology with museum collections - Peers, L; Vitelli, G (Royal Anthropological Institute, 2020)
Material culture provides powerful teaching opportunities for core anthropological themes and issues. Based on experience in teaching both undergraduate and postgraduate students, teh authors provide examples and a framework for a class exercise which supports students to learn from objects and to think anthropologically about them.